High‐Resolution Imaging of Complex Shallow Fault Zones Along the July 2019 Ridgecrest Ruptures. Issue 1 (29th December 2021) - Zhou, Zheng; Bianco, Michael; Gerstoft, Peter; Olsen, Kim
Abstract: We perform ambient noise tomography using data recorded on 342 seismographs within a 50 × 50 km area inside which the July 2019 M7.1 and M6.4 Ridgecrest earthquakes occurred. We used the locally sparse tomography (LST) method, an unsupervised machine learning approach that learns to represent small‐scale geophysical structures using only data from the immediate study. The Rayleigh group speed obtained from LST better predicts travel times than conventional regularized least squares inversion. The 3D shear velocity model of the area obtained from the surface wave dispersion maps reveals a highly heterogeneous low‐velocity zone (with the primary velocity reduction in the upper 2–3 km) around the causative faults for the M7.1 and M6.4 events, with a 40% reduction of the shear wave velocity. Further, correlation of other imaged LVZs in the model area with parts of the Little Lake Fault System without recent activity may indicate long‐lasting damage zones. Plain Language Summary: We perform ambient noise tomography in the region surrounding the surface ruptures of the 2019 Ridgecrest M7.1 and M6.4 earthquakes. The imaging method uses locally sparse tomography (LST), a machine learning‐based method that directly learns the seismic travel time information from the data obtained from a coarse regional array and several dense arrays, with 342 seismic stations in total. The Rayleigh group speed obtained from LST outperforms the conventional regularized least‐squared inversion in travel time predictions and provides more details of the small‐scale geophysical structure. The 3D shear wave velocity model resulting from our imaging reveals a low velocity zone (LVZ) up to 5 km in width and ∼5 km deep surrounding the surface expressions of the 2019 Ridgecrest earthquakes. The average velocity inside the LVZ is 40% lower than that for the surrounding material. The relatively wide LVZ obtained from our imaging is strongly correlated with the distributed faulting from geological and geodetic observations, suggesting an origin as fault damage zones. We find correlation of other imaged LVZs in the model area with faults that have not experienced recent activity. Therefore, if these LVZs represent fault damage zones, they may have persisted for hundreds, maybe thousands of years. Key Points: We find a heterogeneous, up to 5 km wide low‐velocity zone around the 2019 Ridgecrest earthquake sequence using ambient noise tomography The locally sparse imaging technique better predicts travel times than conventional regularized least squares inversion Correlation of the low velocity zone with observed distributed faulting suggests an origin as fault damage zones